Morphophonemic Analysis on Postpositional Affixes in Kamano Language of Papua New Guinea: An Item and Process Approach - Najmatul Wardah; Agus Subiyanto (Master Program in Linguistics, Diponegoro University, 2019)
Kamano language, as one of the language in Papua New Guinea is considered as the pidgin language. This paper aims to identify the morphophonemic phenomena occurs in Kamano language by using the Item and Process model with suffix attachment to show the postpositional markers. This study uses descriptive qualitative as the approach to analyze Kamano language. The result shows that there are six phonological processes from seven morphological rules identified from the affix attachment. Furthermore, there are six phonological rules (1) the deletion of nasal sound [n]; (2) the substitution of glottal sound [ʔ] to the lateral sound [r]; (3) the deletion of vowel sound [a]; (4) the substitution of nasal sound [n] to the nasal sound [m]; (5) the substitution of plosive sound [t] to the lateral sound [r]. the phonological processes which occur mostly in this language are assimilation of place of articulation and manner of articulation.